Fire from the Holy Mountain - Adimora-Ezeigbo, Akachi (University Press Plc, 2007)
In the land of Goshe lived a king who had four wives. For many years, the cry of a baby was not heard in the king's palace. None of his wives could give him a child. The king invited many doctors to examine the women to find out why they could not give him children. However, he did not allow the doctor to examineone of the wives because he hated her...
Keywords: Folktales